The location of the high- and low-affinity bilirubin-binding sites on serum albumin: ligand-competition analysis investigated by circular dichroism - Goncharova, Iryna; Orlov, Sergey; Urbanová, Marie (Biophysical chemistry, 2013)
The locations of three bilirubin (BR)-binding sites with different affinities were identified as subdomains IB, IIA and IIIA for five mammalian serum albumins (SAs): human (HSA), bovine (BSA), rat, (RSA), rabbit (RbSA) and sheep (SSA). The stereoselectivity of a high-affinity BR-binding site was identified in the BR/SA=1/1 system by circular dichroism (CD) spectroscopy, the sites with low affinity to BR were analyzed using difference CD. Site-specific ligand-competition experiments with ibuprofen (marker for subdomain IIIA) and hemin (marker for subdomain IB) did not reveal any changes for the BR/SA=1/1 system and showed a decrease of the bound BR at BR/SA=3/1. Both sites were identified as sites with low affinity to BR. The correlation between stereoselectivity and the arrangement of Arg-Lys residues indicated similarity between the BR-binding sites in subdomain IIIA for all of the SAs studied. Subdomain IB in HSA, BSA, SSA and RbSA has P-stereoselectivity while in RSA it has M-selectivity toward BR. A ligand-competition experiment with gossypol shows a decrease of the CD signal of bound BR for the BR/SA=1/1 system as well as for BR/SA=3/1. Subdomain IIA was assigned as a high-affinity BR-binding site. The P-stereoselectivity of this site in HSA (and RSA, RbSA) was caused by the right-hand localization of charged residues R257/R218-R222, whereas the left-hand orientation of R257/R218-R199 led to the M-stereoselectivity of the primary binding site in BSA (and SSA).
Keywords: Cattle; Animals; skot; Bilirubin; Rabbits; molekulární konformace; Protein Structure, Tertiary; vazebná místa; Amino Acid Motifs; simulace molekulového dockingu; vazba proteinů; hemin; ovce; terciární struktura proteinů; lidé; ibuprofen; Hemin; Protein Binding; Molecular Conformation; sérový albumin; Ligands; Circular Dichroism; Sheep; bilirubin; krysa rodu Rattus; Ibuprofen; Serum Albumin; králíci; zvířata; aminokyselinové motivy; cirkulární dichroismus; Rats; Molecular Docking Simulation; ligandy; Binding Sites; Humans